2015
DOI: 10.1590/s1806-37562015000000021
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anti-smoking laws on high school students in Ankara, Turkey

Abstract: OBJECTIVE: To determine the factors affecting the smoking habits of high school students, their thoughts about changes resulting from anti-smoking laws, and how they are affected by those laws. METHODS: In this cross-sectional study, 11th-grade students at eight high schools in Ankara, Turkey, were invited to complete a questionnaire. RESULTS: A total of 1,199 students completed the questionnaire satisfactorily. The mean age of the respondents was 17.0 ± 0.6 years; 56.1% were female, of whom 15.3% were smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…A recent study with high school students in Ankara demonstrated that 43% of the boys and 15% of the girls were smokers [41]. In our patient group, the ratio of smokers was lower compared to the corresponding age groups based on the current data, but is still considerably high, especially in male adolescent diabetics.…”
Section: Discussioncontrasting
confidence: 64%
“…A recent study with high school students in Ankara demonstrated that 43% of the boys and 15% of the girls were smokers [41]. In our patient group, the ratio of smokers was lower compared to the corresponding age groups based on the current data, but is still considerably high, especially in male adolescent diabetics.…”
Section: Discussioncontrasting
confidence: 64%
“…Having a parents, siblings or friend who smokes and having a family member who smokes at home are also risk factors for adolescents becoming inclined to smoking cigarettes. 3 Within a study conducted by Demir et al 14 with adolescents aged between 15 and 20 years in Ankara, fathers were the most common people in their lives to be smokers (50.4%), this was followed by friends (32.9%). Within our study, 58.8% of the adolescents had a cigarette smoking family member.…”
Section: Discussionmentioning
confidence: 98%
“…Fighting against cigarette smoking, which is a serious public health concern, is of capital importance around the world. 3,14 Within the Global Youth Tobacco Survey conducted by Choi et al 17 in Korea in 2013 with 4235 adolescents aged between 13 and 15 years, it was seen that 66.8% of the adolescents wanted to quit smoking cigarettes. In our study 8 (72.7%) of the 11 adolescents had considered quitting smoking cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies from LMICs to date have demonstrated a decrease in second‐hand smoke exposure with the implementation of SFPs [6,7]. One study from Turkey assessed the association between SFP implementation and smoking cessation in high school students, but found no effect [8]. To our knowledge, effects on smoking cessation among adult smokers in LMICs have not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%